Pendampingan Pembuatan NIB Dan P-IRT Pada UMKM Kripik Singkong Di Desa Kemuning Lor, Kecamatan Arjasa - Fadli, Muhammad; Sunyoto, Doni; Aris Noval, Muhammad; Ridwan Al Fani, Muhammad; Kafi, Muhamad; Nur Fadilah, Siti; Akmala Dewi, Nur; Akmal Firdaus, Radika; Fathurrohman, Wafiq; Marsidi (Shofanah Media Berkah, 2024)
This program was designed to assist MSME (Micro, Small, and Medium Enterprises) operators in Kemuning Lor Village, Arjasa District, in securing essential business legality for their business development. The legal documents needed include the acquisition of a Business Identification Number (NIB) and a Home Industry Food Production Certificate (P-IRT). This initiative, carried out by Group 164 of the Collaborative KKN, employed a comprehensive approach involving methods of observation to grasp initial conditions, educational outreach to provide deeper understanding, and intensive mentoring to ensure that MSME operators could apply the knowledge acquired. The program also aimed to educate MSME operators on the significance of business legality as a means to enhance the competitiveness of their products in wider markets. By utilizing the Online Single Submission (OSS) platform, the licensing process became simpler and more transparent, encouraging MSME operators to promptly manage their business legality. The program's outcomes indicate a significant improvement in MSME operators' understanding and capabilities in handling business legality, ultimately assisting them in expanding their business scale and improving product quality.